Population genomics of honey bees reveals a selection signature indispensable for royal jelly production. (August 2020) - Rizwan, Muhammad; Liang, Pingping; Ali, Habib; Li, Zhiguo; Nie, Hongyi; Ahmed Saqib, Hafiz Sohaib; Fiaz, Sajid; Raza, Muhammad Fahad; Hassanyar, Aqai Kalan; Niu, Qingsheng; Su, Songkun
Abstract: In order to interpret the molecular mechanisms that modulating the organism variations and selection signatures to drive adaptive evolutionary changes are indispensable goals in the new evolutionary ecological genetics. Here, we identified the gene locus associated to royal jelly production through whole-genome sequencing of the DNA from eight populations of honeybees. The analysis of the samples was composed of 120 individuals and each pointed extremely opposite trait values for a given phenotype. We identified functional single nucleotide polymorphisms (SNPs) candidate that might be essential in regulating the phenotypic traits of honeybee populations. Moreover, selection signatures were investigated using pooling sequencing of eight distinct honeybee populations, and the results provided the evidence of signatures of recent selection among populations under different selection objectives. Furthermore, gene ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses indicated that selected genes were potentially involved in several biological processes and molecular functioning, which could directly or indirectly influence the production of royal jelly. Our findings can be used to understand the genomic signatures, as well as implicate a profound glance on genomic regions that control the production trait of royal jelly in honey bees. Highlights: Whole-genome resequencing of DNAs was done from populations of honeybees. Each populations composed of 120 individuals showing extreme opposite trait values for a given phenotype in the same species. Nucleotide polymorphisms (SNPs) within selected are important in regulating the phenotypic traits of honeybee populations. Gene ontology (GO) annotation and KEGG pathway analyses indicated that selected genes are potentially involved in several biological process and molecular functioning, which can directly or indirectly influence the production of royal jelly.